Video Game Influences on Aggression, Cognition, and Attention (Springer International Publishing, 2018)
This book addresses the ongoing scientific debates regarding video games and their effects on players. The book features opposing perspectives and offers point and counterpoint exchanges in which researchers on both sides of a specific topic make their best case for their findings and analysis. Chapters cover both positive and negative effects of video games on players' behavior and cognition, from contributing to violence and alienation to promoting therapeutic outcomes for types of cognitive dysfunction. The contrasting viewpoints model presents respectful scientific debate, encourages open dialogue, and allows readers to come to informed conclusions. Key questions addressed include: · Do violent video games promote violence? · Does video game addiction exist? · Should parents limit children's use of interactive media? · Do action video games promote visual attention? · Does sexist content in video games promote misogyny in real life? · Can video games slow the progress of dementia? · Are video games socially isolating? Video Game Influences on Aggression, Cognition, and Attention is a must-have resource for researchers, clinicians and professionals as well as graduate students in developmental psychology, social work, educational policy and politics, criminology/criminal justice, child and school psychology, sociology, media law, and other related disciplines.